Short social interactions in male Japanese Quail fail to influence temporal dynamics of testicular and adrenocortical activities irrespective of photoperiodic reproductive status - Dominchin, Maria Florencia (2017)
This study evaluates whether short daily male conspecific visits influence the dynamics of endocrine testicular and adrenal photo-responsiveness. A group of male Japanese Quail was exposed to short photoperiods and another group to long photoperiods. The quail exposed to short photoperiods were classified as responsive (SD-R) or non-responsive (SD-NR), depending on whether or not they lost their reproductive condition after 5 weeks of short days (SD). Individuals kept on a long photoperiod were used as controls (LD). After photoperiodic classification and during four consecutive days, individually-caged SDR, SD-NR and LD resident male quail received 5-min visits from photo-stimulated (and therefore sexually active) male quail (social treatment). Cloacal gland volume (CGV), and androgen and corticosterone metabolites (AM and CM, respectively) in droppings were measured bi-weekly and evaluated by repeated measures ANOVA over a 6-week period. Immediately after photoperiodic classification and before social treatment, CGV, AM and CM values showed a SD-R<SD-NR<LD pattern (P<0.001). Along SD exposure, SD-NR quail showed spontaneous cloacal gland recovery and AM and CM concentrations were found to be similar to those of the LD quail. At the end of the study, the SD-R group had still not recovered LD control values. Although the social treatment induced an overall main effect on AM (P<0.02) and CM concentrations (P<0.009), these changes were not related to a particular photoperiodic treatment. These findings provide a novel insight into the social modulation of reproductive and adrenocortical responses, particularly during transition from the photosensitive state to photorefractoriness.